Improving the Production Process of Curry Puff Products to Enhance the Sustainable Potential of Mae Baan Tapon Noi Community Enterprise, Khlung District, Chanthaburi Province - Setsathien, Pratchaporn; Netiworaruksa, Benjamas; Kunsook, Kritiyaporn; Chantri, Pongsaton (NKRAFA JOURNAL OF SCIENCE AND TECHNOLOGY, 2025)
The analysis of the curry puff production process of Mae Baan Tapon Noi Community Enterprise, Khlung District, Chanthaburi Province, using a fishbone diagram found that the main causes were that when the curry puffs were sold, the products were not crispy and there was an excessive waiting time. Therefore, the objective of this research was to study and improve the curry puff production process. From the study and analysis of the production process using a process flow diagram, it was found that it took a total of 14 hours and 15 minutes to produce 30 pieces. Improvements were made based on the ECRS principle, focusing particularly on the filling preparation stage. As a result, the time required for this stage was reduced by 72.30% of the original duration. The production process was revised and divided into two steps: 1) the twice-frying process and 2) the baking process. These two methods were evaluated through sensory quality evaluation method. The results showed that the twice-frying process received the highest overall preference, with an average score of 7.15. The moisture values of the traditional, twice-frying, and baked processes were 13.97, 13.10, and 12.70, respectively. The water activity values of the traditional, twice-frying, and baked processes were 0.787, 0.811, and 0.775, respectively. Therefore, the twice-frying process was selected for the curry puff product manufacturing process.